Mughal Gujarat: An Acme of Learning - Fatma, Sadaf (TAWARIKH, 2015)
ABSTRACT: Here, in this paper, an attempt has been made to examine the extent to which the society and culture in Gujarat, India, was enriched, and how the province became a seat of learning after the incorporation in to the Mughal empire as the place became a conglomeration of a large number of heterogeneous communities, due to its prosperous trade and commerce. The province of Gujarat was annexed to the Mughal empire in 1572 AD (Anno Domini), under the reign of Akbar and became not only most urbanized regions of India, but the most flourishing province of Mughals owing to its overseas trade and commerce. Historians have systematically studied the prosperous economy of Mughal Gujarat and the impact of Mughal annexation on its overseas trade; but, in contrast, the culture of Gujarat under the Mughal rule has not received the attention, it deserves. The main focus of the paper is: to reveal how Gujarat had flourished not only economically, but culturally also became one of the highest seats of learning in Mughal India; to analyse the educational system prevalent in Mughal Gujarat; to explore the role of the intellectuals, literati, and physicians in the society in Gujarat; and what was their patronage network and how they contributed in the rich syncretic culture of Gujarat. The paper further discusses the institutions controlled by the men, in particular âmaktabsâ, âmadrasasâ, and hospitals; and their course of content and forms of instructions etc. In the presence of such a large number of heterogeneous communities, obviously due to its prosperous trade and commerce, Gujarat was culturally âsyncreticâ and âcompositeâ; this is also the central aim of the paper to trace.KEY WORDS: Mughal Gujarat, seat of learning, educational system, patronage network, course of content, forms of instructions, and cultural syncretism.About the Author: Sadaf Fatma is a Research Scholar at the Centre of Advanced Study, Department of History AMU (Aligarh Muslim University), Aligarh 202002, Uttar Pradesh, India. For academic interests, the author is able to be contacted via e-mail at: amusadaf@gmail.comHow to cite this article? Fatma, Sadaf. (2015). âMughal Gujarat: An Acme of Learningâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.75-86. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (January 22, 2015); Revised (May 22, 2015); and Published (October 28, 2015).